Pengaruh Gaya Belajar dan Kecerdasan Emosional Terhadap Kemampuan Pemecahan Masalah Matematika di MA Putra Al-Ishlahuddiny - Gustiana, Hikmatul; Hardiani, Nur; Hesikumalasari, Hesikumalasari (Jurnal of Math Tadris, 2023)
This research aims to determine the influence of learning style and emotional intelligence on mathematical problem solving abilities on the subject of trigonometry comparisons in the 2013 curriculum learning. Quantitative research using the Expost Facto method. The sample in this study was 91 MA Putra Al-Ishlahuddiny class X students using random sampling technique. The research instruments used were a learning styles questionnaire, an emotional intelligence questionnaire and a mathematical problem solving ability test. Based on the results of the two-way ANOVA test, the following results were obtained: (1) There was no influence of students' learning styles on mathematical problem solving abilities in trigonometry material for MA Putra Al-Ishlahuddiny students. (2) There is an influence of students' emotional intelligence on mathematical problem solving abilities in the trigonometry material of MA Putra Al-Ishlahuddiny students. (3) There is no interaction effect between learning style and students' emotional intelligence on mathematical problem solving abilities in trigonometry material for MA Putra Al-Ishlahuddiny students.